KESIAPAN KERJA DALAM KEPRIBADIAN ISLAMI MAHASISWA - Fadillah, Haris; Istati, Mufida (JURNAL KONSELING GUSJIGANG, 2017)
This research is field research (field research) is qualitative, that is a research that produce descriptive data. The subjects of this study are students of KI-BKI Department of class of 2014. The object of this research is the readiness of work in the Islamic student's personality of KI-BKI force of 2014. Data collection techniques used include interviews, observation, and documentation. Based on the results of data analysis, the research findings show that the readiness of work on aspects of knowledge, skills, and work actions in the Islamic student's personality of KI-BKI force 2014 have good ability. From the results of the research there are some suggestions that are given to the department of KI-BKI to continue to improve efforts in facilitating the development of counselor competence. For KI-BKI students as BK teacher candidates to continue to develop themselves to achieve the expected counselor competence.